To determine which expression is equivalent to \(-3x - 5\), we need to simplify each option and compare it to \(-3x - 5\).
Option A: \[ -1 + (x - 4x) + 6 = -1 + (-3x) + 6 = -3x + 5 \]
Option B: \[ (x - 7) + (2 - 4x) = x - 7 + 2 - 4x = -3x - 5 \]
Option C: \[ (-4x - 6) + (2 + 5x) = -4x - 6 + 2 + 5x = (5x - 4x) + (-6 + 2) = x - 4 \]
Option D: \[ -1 + 3x - (2x + 6) = -1 + 3x - 2x - 6 = (3x - 2x) + (-1 - 6) = x - 7 \]
Now comparing the simplified expressions:
- A simplifies to \(-3x + 5\)
- B simplifies to \(-3x - 5\) (this is equivalent to our original expression)
- C simplifies to \(x - 4\)
- D simplifies to \(x - 7\)
The expression which is equivalent to \(-3x - 5\) is Option B.